UJI AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BATANG SEKILANG (Embelia borneensis Scheff) TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus MENGGUNAKAN METODE DISC DIFFUSION - Goetie, Inayah Herman; Sundu, Reksi; Supriningrum, Risa (Jurnal Riset Kefarmasian Indonesia, 2022)
Sekilang is one of the plants in North Kalimantan and is found in the Ampan Ibau Forest. This plant is empirically used by the people of Long Temuyat Village as a poison from natural ingredients to catch fish and as a leech repellent. The content of active compounds in sekilang bark extract include alkaloids, tannins, saponins, flavonoids. These compounds have the potential as antibacterial, so it is necessary to test the antibacterial activity. The purpose of this study was to determine the antibacterial activity of the sekilang bark extract against Escherichia coli and Staphylococcus aureus bacteria. The research phase included plant determination, sample collection, maceration extraction, and antibacterial activity test using the disc diffusion method with extract concentrations of 20%, 30%, and 40%. The results showed that the ethanol extract of the bark of sekilang has the potential to inhibit bacterial growth. The antibacterial activity of the bark extract of the cruciferous plant against Escherichia coli bacteria at concentrations of 20%, 30% and 40%, respectively, was 5.9 mm, 6.7 mm and 5.9 mm. Meanwhile, the activity of the bark extract against Staphylococcus aureus at concentrations of 20%, 30% and 40%, respectively, was 7.6 mm, 6.8 mm and 8.0 mm. The antibacterial activity of the bark extract against both bacteria was included in the moderate criteria.